2011
DOI: 10.1002/ps.2311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of boscalid‐ and penthiopyrad‐resistant isolates of Didymella bryoniae and assessment of their sensitivity to fluopyram

Abstract: The genotype-specific cross-resistance relationships between the SDHIs boscalid and penthiopyrad and the lack of cross-resistance between these fungicides and fluopyram should be taken into account when selecting SDHIs for gummy stem blight management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 15 publications
4
57
1
2
Order By: Relevance
“…However, it should be emphasized that different levels of sensitivity to SDHIs were found in closely related species D. bryoniae. [32][33][34][35] The EC 50 values of fluopyram, established by Avenot et al [32] were homogeneous and far lower (0.020-0.189 mg L ¡1 ) than these obtained in the present study. In terms of sensitivity to boscalid, Thomas et al [33,34] found 82 very highly resistant and seven highly resistant D. bryoniae isolates using the discriminatory concentration of 3 mg L ¡1 .…”
Section: Discussioncontrasting
confidence: 68%
“…However, it should be emphasized that different levels of sensitivity to SDHIs were found in closely related species D. bryoniae. [32][33][34][35] The EC 50 values of fluopyram, established by Avenot et al [32] were homogeneous and far lower (0.020-0.189 mg L ¡1 ) than these obtained in the present study. In terms of sensitivity to boscalid, Thomas et al [33,34] found 82 very highly resistant and seven highly resistant D. bryoniae isolates using the discriminatory concentration of 3 mg L ¡1 .…”
Section: Discussioncontrasting
confidence: 68%
“…To date, S. cucurbitacearum has been identified only in temperate regions and is more often associated with Cucurbita species (Stewart et al 2015). Although S. citrulli is the dominant gummy stem blight species worldwide, both S. caricae and S. citrulli have been found within watermelon fields in Georgia, USA, where the two species vary in sensitivity to different fungicides (Avenot et al 2012;Li et al 2015). Leaf spot and fruit and stem rot of papaya, also caused by S. caricae (syn.…”
Section: Introductionmentioning
confidence: 96%
“…Although there are multiple benefits of using modern techniques for testing fungicide sensitivity, a standard protocol for boscalid has not been established yet due to the complex responses of many fungi exposed to the fungicide. Indeed, for some fungi, the most critical stage for testing boscalid is the spore germination and germ tube elongation (28,41) whereas, for others, the most sensitive stage is the mycelial growth (6,9).…”
mentioning
confidence: 99%